Ethical Leadership and Self-Efficacy on Police Officers' Performance: The Role of Mediation Perceived Organizational Support - Sila, Andi Zaisal P; Fajriah, Yana; Sukarno, Zulfikry (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study purpose to examine and analyse the influence of ethical leadership and self-efficacy on police performance through perceived organizational support. A quantitative research approach with non-probability sampling was used. A total of 81 members of the Gowa Police Resort were surveyed using a questionnaire. The collected data were then analysed using Structural Equation Modelling-Partial Least Square. The results showed that ethical leadership and self-efficacy do not have a direct effect on police performance. However, the results differed when mediated by the perceived organizational support variable, which had a significant effect on personnel performance. Meanwhile, the direct influence of the variables ethical leadership and self-efficacy on perceived organizational support is significant, as is the variable perceived organizational support on the performance of police members. The implications of this study indicate that improving performance needs to be directed towards strengthening organizational support through the provision of work facilities, clear guidance, attention to personnel needs, recognition of contributions, enhancement of internal communication, continuous development, and the creation of a conducive work environment that supports the optimal execution of tasks